Paradigma Baru Perdagangan Karbon: Mengkaji Peraturan Menteri LHK No. 21/2022 Dari Perspektif Ta'wid dan Polluter Pays Principle - Putri Herawati, Sesi; Triana, Nita; Yaqin, Ainul (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2025)
The carbon trading mechanism as stipulated in the Minister of Environment and Forestry Regulation No. 21 of 2022 is understood as the buying and selling of carbon emission credits that exceed the threshold. In the eyes of Islamic law, carbon trading can be considered as buying and selling, but it does not seem to be fully appropriate. This study aims to analyze how carbon trading is considered as ta'wid (compensation) in the carbon trading mechanism in Permen LHK No. 21 of 2022. Using a normative approach, this research examines the provisions in the Minister of Environment and Forestry Regulation No. 21 of 2022 by comparing it with the concept of ta'wid in Islamic law. The results show that the sale and purchase referred to in Ministerial Regulation No. 21 of 2022 is understood as the sale and purchase of carbon emission credits that exceed the threshold, a concept that in the framework of environmental law is known as the Polluter Pays Principle. Companies that release carbon must pay losses to carbon sinks or have residual carbon, this can be seen as a form of compensation or indemnity related to environmental damage that harms society. Thus, the view that carbon trading as a ta'wid is in line with both sharia economic law and environmental law.